Pengajaran Makna Kata Telanjang Berdasarkan Kejadian 3:1-7 - Hestyn Natal Istinatun; Ragil Kristiawan; Muner Daliman; Junio Richson Sirait (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2021)
Genesis 3:1-7 is the most important of the four chapters in the chapter. The problem that occurred was when the woman in the garden came face to face with a snake who said to her, “you will never die” (Gen 3:4). These words resulted in a dialogue that made the woman not only see and think that the fruit gave understanding, but she also took, ate and gave it to her husband and her husband ate it (Gen 3:6). This action has caused their eyes to be opened so that they know that they are naked (Gen. 3:7a), and they make their loincloths, because naked is a picture of their sinful condition. Meanwhile the LORD God had announced His Law “…in the day that you eat of it, you shall surely die” Genesis 2:17.